Upaya Peningkatan Hasil Belajar Fiqih Materi Zakat dengan Metode Demonstrasi - Sihabudin; Aminudin; Asep Kuswara, Mochamad; Apit, Muhamad (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
The low level of students' understanding of zakat material poses a major challenge in fiqh learning at MAS PP Darussalam Kunir. The dominant lecture method, which is one-way and lacks interactivity, causes students to struggle in comprehending the concepts of nishab and zakat calculation. This learning process requires a more applicative approach to ensure that students not only understand the theory but are also able to apply it. This study aims to improve students' learning outcomes in fiqih lessons on zakat by implementing the demonstration method as a solution. This research employs Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. Data collection was carried out through pre-tests, post-tests, observations, interviews, and documentation. Data analysis was conducted descriptively and quantitatively to measure the improvement in students' learning outcomes, and qualitatively to analyze the dynamics of the learning process. The results show that the demonstration method significantly improved learning outcomes. The average pre-test score in the first cycle was 44.5, increasing to 68.7 in the post-test. In the second cycle, the average pre-test score reached 69.7, with the post-test score rising to 81.6. Moreover, students were more motivated, better understood the material, and were active during the learning process. This method of demonstration has proven effective in addressing the challenges of teaching fiqh of zakat.